Transnational economic behavior of muslim diasporas in the west: the case of french muslims - Refas, Salim (Ankara Sosyal Bilimler Üniversitesi, 2022)
The number of international migrants is estimated to be almost 272 million globally (IOM, 2020), with nearly two-thirds being labor migrants. A significant proportion of these migrants are Muslims who have left their native countries to live in the West. For the specific case of France, this population ranges between 4.7 to 5.1 million according to recent surveys, i.e. about 8% of the total population of the country. This paper is concerned about the present and future of these communities and aims at answering the specific question of their changing transnational economic behavior in today’s world economy. The paper hypothesizes that the international economic decisions of migrants are no longer explained by origin and destination country pairs only but also in relation to other countries with both higher and lower wages. A simple microeconomic framework is proposed to explain how these migrant populations make rational choices about their decision to permanently stay, migrate back to their country of origin or migrate to a third country. The model identifies successive waves of migrants with differentiated economic behavior. In particular, a specific class of migrants is identified for which wage differentials are not the main driver of migration or remigration decisions due to the inelasticity of their labor demand to wages. These migrants rather seek to create and manage their own companies and invest in a better comfort of living in countries other than France. Descriptive statistics demonstrate the potential for such framework to explain simultaneously the observed increasing migrations of French Muslims to high-income countries driven by wage differentials, a rapidly expanding migration to Turkey and Malaysia, and a resurgence of migration to former colonies which had previously experienced a consistent reduction in migration flows since the 1980s. The paper also estimates the economic impact of remigrations of Muslims from France, which represents today a minimum of €5.5 billion on annual basis, and calls for more research in these hybrid migration decisions to better analyze and map the future economic behaviors of Muslim populations in the West.
Keywords: Migrations; Diaspora; Transnationality; Hybrid migrations; French muslims